Sword of Christ. Christian inspirations of Polish socialism before the January Uprising - KULIGOWSKI, PIOTR (Journal of Education Culture and Society, 2020)
The article presents the history of the Christian fraction of Polish sociali sm against the background of the era, from the very beginning until its end after the January Upris ing. On the basis of the texts from the era the understanding of socialism, the principles of the program of Clusters of the Polish People and the anatomy of Fr. Piotr Ściegienny’s conspiracy have been reconstructed. The text reproduces the utopian ideas of social reconstruction by Zenon Świętosławski and Ludwik Królikowski and based on these the text also shows the place of Christian socialism in the Polish socialist thought.